ANALISIS MINAT BELAJAR SISWA MTS KELAS VII DALAM PEMBELAJARAN MATEMATIK MATERI ALJABAR BERDASARKAN GENDER - Asiah Badriyatur Rojabiyah; Wahyu Setiawan (Departement of Mathematics Education, 2019)
This study was conducted to analyze the learning interest of class VII MTS students in mathematics learning algebra based on gender by using indicators of learning interest namely feeling happy, student interest, student involvement, diligent in learning and doing mathematical assignments, diligent and learning discipline and having a study schedule. The method used for analysis in this study is a Qualitative Descriptive Method using a Likert scale with the provision of instruments in the form of a questionnaire conducted to analyze students' learning interest in mathematical learning. The population in this study were MTS students in Cikalongwetan and the samples studied were one of the classes totaling 29 students in class VII of MTS Al-Barry Cikalongwetan. The instrument used for this research is the giving of questionnaires to each student. The results of the analysis obtained in this study that there are differences in students' interest in learning in mathematical learning algebraic material, where male students have a better interest from women.